Pengaruh Dosis Molase dan Probiotik Lactobacillus Sp. terhadap Laju Pertumbuhan dan Kelangsungan Hidup Benih Ikan Nila (Oreochromis niloticus) - Mirna, M; Tahir, Rahmawati (Fakultas Pertanian, Peternakan dan Perikanan Universitas Muhammadiyah Parepare, 2023)
This present study investigates the combination of probiotic Lactobacillus sp. and molasses applied to promote growth performance and survival of Nile Tilapia seed. Probiotic could act as an additive agent for fish seed with incomplete digestive organ development as it produces the digestion-support enzyme. The experiment was set based on the formalized fish feed, consisting of A (no molasses and probiotic provision), B (2 r/L molasses), C (108 cfu/mL probiotic), D (108 cfu/mL probiotic + 4 r/L molasses), E (1010 cfu/mL probiotic + 2 r/L molasses) and applied in three replicates each. Fish were reared in cone bottom tanks and were fed according to the treatment (2 times a day in 3 weeks). The growth and survival rate data were collected during the experiment and were analyzed using ANOVA (analysis of variance). The results indicate significant growth and survival of Nile Tilapia seed (P<0,05) generated by the enhancement of probiotics and molasses into fish feed with formalized 1010 cfu/mL probiotic + 2 r/L molasses.